2020
DOI: 10.1002/csc2.20361
|View full text |Cite
|
Sign up to set email alerts
|

Selection of potato clones for heat tolerance and resistance to potato viruses X and Y for processing purposes

Abstract: Potato (Solanum tuberosum L.) is one of the most important crops for human consumption worldwide, representing an essential component for the food security of several countries. However, yield and quality are negatively affected by biotic and abiotic stresses. In this sense, the selection of potato cultivars tolerant to heat and resistant to diseases is of great importance. Our goal was to select clones suitable for the chips industry, having heat tolerance and bearing the Rx1 and Ryadg alleles, which confer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 51 publications
(87 reference statements)
0
27
0
Order By: Relevance
“…Fernandes Filho et al [37] used variations in seasonal temperatures to characterize the response of potato (Solanum tuberosum L.) to higher temperatures in Brazil. The plants were grown across three seasons from January to May 2017, May to September 2017, and November 2017 to February 2018, representing moderate heat stress, no heat stress, and severe heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes Filho et al [37] used variations in seasonal temperatures to characterize the response of potato (Solanum tuberosum L.) to higher temperatures in Brazil. The plants were grown across three seasons from January to May 2017, May to September 2017, and November 2017 to February 2018, representing moderate heat stress, no heat stress, and severe heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the estimation of heritability for breeding populations grown under stresses, it has been reported that the greater the level of stress to which the plants are subjected, the lower the heritability estimates (Fernandes Filho et al, 2021; Hoffmann & Merila, 1999; Mwadzingeni et al, 2017). Hence, it poses a challenge in selecting drought‐resistant genotypes when they are subjected to long periods of drought.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes Filho et al. (2021), seeking potato clones suitable for industry, and Melo et al. (2020), aiming to select superior common bean progenies to mitigate the effects of genotype‐environment interactions, incorporated a restriction on the selection index for multiple traits based on the genotype‐ideotype distance.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes Filho et al. (2021) observed that the proportion of agreement between direct selection and the FAI‐BLUP index increased as the intensity of selection also increased, reaching between 59% and 73% when applying a selection intensity of 50%. These results demonstrate that the index was efficient in the selection of the best seedless table grape hybrids.…”
Section: Discussionmentioning
confidence: 99%